2002
DOI: 10.1056/nejmoa012918
|View full text |Cite
|
Sign up to set email alerts
|

Blood Levels of Long-Chain n–3 Fatty Acids and the Risk of Sudden Death

Abstract: The n-3 fatty acids found in fish are strongly associated with a reduced risk of sudden death among men without evidence of prior cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
615
8
25

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,008 publications
(684 citation statements)
references
References 24 publications
30
615
8
25
Order By: Relevance
“…In addition, energy intake and the total amount of food consumed are usually smaller among women and therefore fish may be able to partially replace other types of meats in their diet. With regard to poultry consumption in previous studies, those who had the highest fish consumption had the highest consumption of poultry (17,23,27,29,49) . In the present study, this association was seen only in the general population, although the positive linear association practically disappeared especially among the women after adjusting for other food groups.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, energy intake and the total amount of food consumed are usually smaller among women and therefore fish may be able to partially replace other types of meats in their diet. With regard to poultry consumption in previous studies, those who had the highest fish consumption had the highest consumption of poultry (17,23,27,29,49) . In the present study, this association was seen only in the general population, although the positive linear association practically disappeared especially among the women after adjusting for other food groups.…”
Section: Discussionmentioning
confidence: 90%
“…It is in that respect noteworthy that the Lemaitre et al (2002) case-control study indicated an association between TFA intake and SCD. n-3 PUFA contrastingly decrease the risk of SCD (Valagussa et al, 1999;Albert et al, 2002). These effects could be due to changes in membrane fatty acid composition in cardiac conductory or contractile cells (Patel et al, 2001;Katz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These opposing effects are seen, on the one hand, in the GISSI-Prevenzione trial where a reduction in total mortality and sudden cardiac death (SCD) was found in post-AMI patients supplemented with marine n-3 PUFA (Marchioli et al, 2002), and in the Physicians' Health Study with a strong negative association between blood levels of long-chain n-3 PUFA and the risk of subsequent SCD (Albert et al, 2002). Other studies have demonstrated a positive effect of n-3 PUFA on cardiovascular mortality (Burr et al, 1989;de Lorgeril et al, 1999;Valagussa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, additional analyses in a larger cohort is required to confirm this. Nevertheless, this suggests that an individual's omega-3 status, including a DBS collection followed by rapid transesterification time of no more than one minute-and potentially less-combined with fast gas chromatography [26] could provide an assessment of cardiovascular disease risk [10] in less than 1 h. This rapid profiling and reduced monetary requirement makes fingertip prick blood collections an exciting tool for future use in clinical settings to provide rapid feedback to patients in need of dietary improvement or compliance confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the % sum of eicosapentaenoic acid (EPA, 20:5n-3) + docosahexaenoic acid (DHA, 22:6n-3) in whole blood can be used as a predictor for risk of sudden cardiac death [10].…”
Section: Introductionmentioning
confidence: 99%